ETHANOLIC EXTRACT OITMENT OF THE GRAPTOPHYLUM PICTUM L GRIFF LEAVES AS ANALGESIC AGENT TO MALE WHITE RAT - Rikomah, Setya Enti; Fitri, Ninsi (Oceana Biomedicina Journal, 2020)
Graptophyllum pictum L Griff Leaves in the community are used as medicinal ingredients, one of which is for analgesics. Black pudding leaves contain secondary metabolite compounds that act as suspected analgesics, namely flavonoids. The ethanolic extract of black pudding leaves has been formulated into cream and ointment preparations. The purpose of this study was to determine the effectiveness of analgesic preparations of black pudding leaves (Graptophyllum pictum L. Griff) ethanol extract in white male mice. The effectiveness of analgesics was tested using the hotplate method. The test animals used were 25 white male mice which were divided into 5 groups: negative control (F0), positive control (Ichtiol® ointment), and black pudding leaf F1 (10%), F2 (15%) ethanol extract treatment group, and F3 (20%). Observation of stretching of mice was done after the feet of mice were induced and immediately given treatment. Observation of analgesic percentage in each mouse was carried out every 5 minutes for 60 minutes. The data obtained were processed and analyzed using one-way ANOVA and Duncan test with a 95% confidence level. One-way ANOVA test results showed that there were significant differences between treatment groups (0.003 <0.05). The results of the average percentage of analgesic effectiveness of formula 2 have a good effect that is equal to 77.969%. Duncan's test results showed that the group that gave the best analgesic effectiveness was formula 2 (15%) comparable to positive control.Keywords: Graptophyllum pictum,  Analgesics, ointment, Hotplate.